Drug use in the family: impacts and implications for children (ANCD Research Paper No. 13) - Moss, D; Frye, S; Dawe, S; Best, D; Atkinson, J (My University, 2006)
The impact of parental substance misuse, specifically alcohol and illicit drug use, on children aged between two and 12 years is examined. The report contains a review of the literature on prevalence of substance misuse in families and analyses the National Drug Strategy Household Survey and National Health Survey, the Longitudinal Study on Women's Health, the Longitudinal Study of Australian Children, and specialist population databases. Use of alcohol and other drugs in households with dependent children was found to be high, with high rates of binge drinking in particular. While parental substance misuse can affect many aspects of a child's life, it is generally difficult to disentangle the effects of parental substance use from broader social and economic factors that contribute to and maintain the misuse of either drugs or alcohol. A separate chapter investigates the effects of parental substance misuse on Indigenous children.
Keywords: Health; Health -- Addictive behaviours; Health and wellbeing; Health; Addictive behaviours; Health and wellbeing